Bifunctional Catalysts Based on Tungsten Hydrides Supported on Silicated Alumina for the Direct Production of 2, 3‐Dimethylbutenes and Neohexene from Isobutene. Issue 12 (6th April 2017) - Larabi, Cherif; Garron, Anthony; Rouge, Pascal; Szeto, Kai C.; Norsic, Sébastien; De Mallmann, Aimery; Merle, Nicolas; Taoufik, Mostafa
Abstract: Well‐defined bifunctional supported catalysts that comprise tungsten hydride moieties and Brønsted acid sites were prepared successfully. The catalysts showed outstanding activities and selectivities toward the formation of high‐value‐added products, 2, 3‐dimethylbutenes and 3, 3‐dimethylbutene, through a combination of the metathesis and dimerization of isobutene. The relationship between the physicochemical properties of the catalysts and their activities and selectivities indicated that isobutene conversion increased from 4 to 95 % as a function of the silica content of the silicated alumina (obtained from Sasol). Nevertheless, the selectivity toward branched hexenes showed a volcano‐shaped curve that presented a maximum for the catalyst with 5 wt % silica. Therefore, the control of the support acidity by the silica loading on alumina resulted in an increase of the selectivity toward neohexene. Abstract : Cat got your tungsten? We study the influence of the acidic properties of silicated alumina on the catalytic performances of supported tungsten hydride catalysts for isobutene conversion. The positive effect of moderate doping on the catalytic productivity is evidenced. Indeed, the sample with 5 wt % of SiO2 allows us to obtain high selectivities to 2, 3‐dimethylbutenes and neohexene.